Evaluation of anemia in pregnant women based on SIMKIA SEMBADA data at 3 Health Centers in Sleman-Yogyakarta District - Rezatiara, Ulva; Kandarina, Istiti; Rahmawati, Vista Ari (BKM Public Health and Community Medicine, 2021)
Background: Pregnant women are a vulnerable group who experience anemia, increasing the risk of short births and low birth weight babies. In a pandemic situation with the PPKM policy (Enforcement of Community Activity Restrictions), pregnancy examination services (integrated ANC) for pregnant women will still be carried out in accordance with health protocols. In antenatal care (ANC) services for pregnant women, health workers must provide quality services according to the SOPs. Objective: To evaluate anemia in pregnant women based on SIMKIA SEMBADA data. Methods: Data were collected through secondary data at SIMKIA SEMBADA and observation, and data were analyzed using descriptive statistics. Results: There are 3 out of 25 Puskesmas in Sleman Regency, which continues to experience a constant increase in anemia prevalence from 2016-to 2020, namely Seyegan Health Center, Gamping-1 Health Center, and Gamping-2. Judging from the recording and reporting of ANC on the SIMKIA SEMBADA application from 90 anemic pregnant women who have given birth, 3% of babies are born with low birth weight, and 21% of babies are short. Pregnant women with anemia mostly occur in the age range of 20-35 years. Judging from the history of ANC visits, pregnant women in the three puskesmas areas have performed ANC since the first trimester of pregnancy. However, pregnant women still carry out early pregnancy checks in the 2nd and 3rd trimesters. Anemic pregnant women who receive ANC services, according to SOPs, are still low, below 77%. Conclusions and Suggestions: From SIMKIA SEMBADA data, there are still anemic pregnant women who are recorded as not having their HB checked according to the contents of the SOP for the management of anemic pregnant women; therefore, it is necessary to update the policy references in the SOP such as the policy of the Minister of Health of the Republic of Indonesia No. 97 of 2014 and Regulation of the Regent of Sleman No. 15 of 2021 as well as re-socializing the implementation of SOPs aimed at improving service quality and optimizing service outcome data.